Can pleural packing be an effective solution for uncontrollable intra or post-operative hemorrhage - Zribi, Hazem; Ammar, Abderrahmen; Abdelkbir, Amina; Bouacida, Imen; Maazaoui, Sarra; Mestiri, Tahar; Marghli, Adel (International Surgery Journal, 2020)
Background: Uncontrollable bleeding during thoracic surgery has been a challenging problem faced by surgeons. The aim of this study was to clarify the usefulness of pleural packing as a good alternative to control hemorrhage and to deduce the common point between those patients. Methods: This was a retrospective case series study of eight patients who underwent thoracic surgery with uncontrollable intrathoracic haemorrhage and shock which required intrathoracic packing from January 2014 to December 2019. Results: During the study period, eight patients underwent thoracic surgery with uncontrollable intrathoracic haemorrhage and needed packing. Successful hemostasis was achieved in all cases after pleural packing. The mean age was 58.5 years and six patients were males. The common point was the history of pulmonary tuberculosis which was with invasive pulmonary aspergillosis for two patients. Incision was a posterolateral thoracotomy in all cases and six patients required pulmonary resection (five lobectomy and one bilobectomy), one patient required decortication, and one had tumorectomy of a paragonglioma located in the Barety’s space. The unpacking took place right after 48 hours. An arrest of the bleeding was noticed in all the remaining patients. The mean time of the mechanical ventilation was 11 days. Complications included atelectasis and infectious pneumonitis. We noted one case of death. Conclusions: Intrathoracic packing may be an effective and feasible technique in managing uncontrollable post-operative hemorrhage when the life of patients is in danger. This technique should always be considered for patients with tuberculosis history.